The Correlation Between MYO9B Gene Polymorphism and Inflammatory Bowel Disease in the Guangxi Zhuang Population - Zeng RZ (Dove Medical Press, 2021)
Rui-zhi Zeng,1 Xiao-dan Lv,2 Geng-feng Liu,1 Guang-li Gu,1 Shi-quan Li,1 Lan Chen,1 Jun-hua Fan,1 Zhao-liang Liang,1 Hui-qin Wang,1 Fei Lu,1 Ling-ling Zhan,2 Xiao-ping Lv1 1Department of Gastroenterology, The First Affiliated Hospital of Guangxi Medical University, Nanning, 530021, Guangxi Zhuang Autonomous Region, People’s Republic of China; 2Department of Clinical Laboratory, The First Affiliated Hospital of Guangxi Medical University, Nanning, 530021, Guangxi Zhuang Autonomous Region, People’s Republic of ChinaCorrespondence: Xiao-ping LvDepartment of Gastroenterology, The First Affiliated Hospital of Guangxi Medical University, No. 6 of Shuangyong Street, Qingxiu District, Nanning, 530021, Guangxi Zhuang Autonomous Region, People’s Republic of ChinaTel +86 135 1788 8390Email pingping98987@111.comObjective: To analyze the correlation between site rs962917 of the MYO9B gene and inflammatory bowel disease (IBD) in the Guangxi Zhuang nationality population.Methods: The intestinal mucosa tissue of 153 IBD subjects (Han and Zhuang patients only) in the Guangxi Zhuang autonomous region comprised the case group, and the intestinal mucosa tissue of 155 healthy subjects (Han and Zhuang patients only) in the same region represented the control group. Deoxyribonucleic acid was extracted from the intestinal mucosa tissue of each experimental group, and the MYO9B gene-target fragment containing the single nucleotide polymorphism (SNP) site rs962917 was designed. Finally, polymerase chain reaction products were obtained by amplification, analyzed, and compared using the sequencing results.Results: The results indicated that the genotype frequency of the MYO9B SNP site rs962917 between Crohn’s disease (CD) and control groups of Zhuang and Han participants differed significantly (P < 0.05). Furthermore, the genotype frequency of MYO9B site rs962917 differed significantly between the Zhuang and Han population groups (P < 0.05).Conclusion: Site rs962917 of the MYO9B gene is related to CD susceptibility and incidence among the Guangxi Zhuang population.Keywords: inflammatory bowel disease, IBD, ulcerative colitis, UC, Crohn’s disease, CD, MYO9B gene, gene polymorphism